Transformation of Social Values in Political Policy: A Case Study of Community Participation in Regional Development - Karjo Nalu; Achmad Zahruddin; Suripto; Yudhi Anggoro (Journal of Politica Governo, 2025)
Abstract Modernization and globalization have shifted the pattern of community participation in regional development from community-based to more formal structural mechanisms. This shift increases the effectiveness of regulation and distribution of resources, but also limits the flexibility and room for community movement. Social values that shift from collectivism to individualism also influence the level of political awareness, although not always accompanied by an increase in active participation. The main obstacles to community participation include low education, limited access to information, complex bureaucracy, and minimal trust in the government due to corruption. On the other hand, transparency of information and the use of technology, such as e-Musrenbang, have the potential to increase citizen involvement in the development process. Other challenges include the dominance of political elites and unequal access to public policies, which often limit deliberative democracy. Therefore, bureaucratic reform and more effective coordination between agencies are needed to encourage meaningful participation. Openness of information and increased political and digital literacy are key factors in creating a more inclusive space for participation. With the right strategy, community participation can grow substantially and contribute to more transparent, democratic, and sustainable regional development.